Pengaruh Gaya Kepemimpinan, Kompensasi dan Lingkungan Kerja terhadap Kinerja dengan Motivasi Sebagai Variabel Intervening - Rizki Reza Satria; Deden Mulyana; Asep Yusup Hanapiah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine the effect of leadership style, compensation and work environment on performance with motivation as an intervening variable. The study was conducted on employees at the Branch Collection Unit & Recovery Asset Sales of PT Bank Tabungan Negara, West Java Regional Office. Sampling was carried out using saturated sampling technique, with a total sample size of 123 samples, which were spread across 10 offices of PT. Bank Tabungan Negara, West Java Regional Office. The research instrument used was a questionnaire with a Likert scale. The analysis technique used structural equation modeling with the smartPLS application. The results of this study indicate that, leadership style, compensation, work environment, motivation and performance, in very good condition. Leadership style, compensation and work environment have a positive and significant effect on motivation. Leadership style, compensation and work environment have a positive and significant effect on performance. Motivation has a positive and significant effect on performance. Leadership style, compensation and work environment affect performance with motivation as an intervening variable.